Diffuse unilateral subacute neuroretinitis in a young boy: a case report - Ng, Guan Fook; Abd Aziz, Hayati; Raja Azmi, Mohd Noor; Ahmad Tajudin, Liza Sharmini; Wan Hitam, Wan Hazabbah; Embong, Zunaina (Dove Medical Press, 2012)
We report a case of diffuse unilateral subacute neuroretinitis in a young boy with no clinical visualization of nematode. The diagnosis was made based on clinical findings and detection of Toxocara immunoglobulin G by Western blot test. An 11-year-old Malay boy presented with progressive blurring of vision in the left eye for a duration of 1 year. It was associated with intermittent floaters. Visual acuity in the left eye was 6/45 and improved to 6/24 with pinhole. There was positive relative afferent pupillary defect, impaired color vision, and presence of red desaturation in the left eye. There were occasional cells in the anterior chamber with no conjunctiva injection. Posterior segment examination revealed mild-to-moderate vitritis and generalized pigmentary changes of the retina with attenuated vessels. The optic disk was slightly hyperemic with mild edema. There was presence of multiple, focal, graywhite subretinal lesions at the inferior part of the retina. Full blood picture results showed eosinophilia with detection of Toxocara immunoglobulin G by Western blot test. Investigations for other infective causes and connective tissue diseases were negative. The diagnosis of diffuse unilateral subacute neuroretinitis secondary to Toxocara was made based on clinical findings and laboratory results. He was treated with oral albendazole 400 mg daily for 5 days and oral prednisolone 1 mg/kg with tapering doses over 6 weeks. At 1 month follow-up, the inflammation had reduced, and multiple, focal, gray-white subretinal lesions were resolved; however there was no improvement of vision.